ETIKA BISNIS DALAM LINGKUP PEMASARAN: ETIKA DALAM MELAKUKAN PROMOSI - Prayogo, Devano Vincent; Gunawan, Keevin Philips (Jurnal Pijar, 2024)
Business ethics in the marketing sense are moral guidelines that regulate how companies market their products and services fairly and responsibly. This includes transparency in advertising, honesty in promotions, respect for consumer privacy, and avoiding misleading or harmful practices. Applying business ethics in marketing not only builds consumer trust, but also strengthens a company's reputation and encourages long-term sustainability.